Profil hematologi dan gambaran morfologi darah sapi bali (Bos sundaicus) yang dipelihara di tempat pembuangan akhir alak Kota Kupang - Marsely YD Bunga; Antin YN Widi; Putri Pandarangga (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2019)
Examination of blood profile is very important because the blood has a function in circulatory system and as an indicator for disease but it also helps to monitor the incidence of a disease. The purpose of this study was to determine the hematology profile and blood morphology of the bali cattle (Bos sundaicus) in landfills alak kota Kupang. There are 24 samples of bali cattle were divided in three group: eight cows with age range from 0 to 1.5, eight cows with age range from 1.5 - 3 and eight samples with age range age > 3 years. Parameters were observedusing a hematology autoanalyzer: the number of erythrocyte, leukocyte, hemoglobine, PCV, MCV, MCH, and MCHC; and morphological blood profile was examined using blood smear methods. The results of this study showed normocytic, microcytic, macrocytic, the value of MCH high, hyperchromic and leukocyte counts more higher than normal. Erythrocyte morphological abnormalities were found in this research such as macrocytosis, microcytosis, spherositosis, acanthositosis, burr crenation cell / echinocytes, tear drop cells and hypochromasia. The data obtained are presented in tables and images were analyzed descriptively.